Chromatin Remodeling Factor BRG1 Regulates Stemness and Chemosensitivity of Glioma Initiating Cells. (12th November 2018) - Ganguly, Debolina; Sims, Michelle; Cai, Chun; Fan, Meiyun; Pfeffer, Lawrence M.
Abstract : Glioblastoma multiforme (GBM) is a highly aggressive and malignant brain tumor that is refractory to existing therapeutic regimens, which reflects the presence of stem-like cells, termed glioma-initiating cells (GICs). The complex interactions between different signaling pathways and epigenetic regulation of key genes may be critical in the maintaining GICs in their stem-like state. Although several signaling pathways have been identified as being dysregulated in GBM, the prognosis of GBM patients remains miserable despite improvements in targeted therapies. In this report, we identified that BRG1, the catalytic subunit of the SWI/SNF chromatin remodeling complex, plays a fundamental role in maintaining GICs in their stem-like state. In addition, we identified a novel mechanism by which BRG1 regulates glycolysis genes critical for GICs. BRG1 downregulates the expression of TXNIP, a negative regulator of glycolysis. BRG1 knockdown also triggered the STAT3 pathway, which led to TXNIP activation. We further identified that TXNIP is an STAT3-regulated gene. Moreover, BRG1 suppressed the expression of interferon-stimulated genes, which are negatively regulated by STAT3 and regulate tumorigenesis. We further demonstrate that BRG1 plays a critical role in the drug resistance of GICs and in GIC-induced tumorigenesis. By genetic and pharmacological means, we found that inhibiting BRG1 can sensitize GICs to chemotherapeutic drugs, temozolomide and carmustine. Our studies suggest that BRG1 may be a novel therapeutic target in GBM. The identification of the critical role that BRG1 plays in GIC stemness and chemosensitivity will inform the development of better targeted therapies in GBM and possibly other cancers. Abstract : BRG1 maintains stemness in GICs. BRG1 is essential for maintaining GICs in a stem-like state. BRG1 negatively regulates TXNIP expression in GICs and thereby promotes the expression of genes involved in glycolysis, which is a pathway critical in cancer metabolism. In addition, BRG1 also promotes GIC chemoresistance by modulating MGMT expression. In GICs, the loss of BRG1 leads to increased TXNIP expression, consequently decreasing the expression of glycolytic genes. BRG1 loss in GICs also decreases GIC stemness and leads to lineage-specific differentiation. In addition, loss of BRG1 leads to decreased MGMT expression and thereby enhances GIC chemosensitivity.